Wangun Visual Concept In Pawukon Figures And Interior Design Contexts - Rahmanu Widayat (Mudra: Jurnal Seni Budaya, 2018)
Many of cultural heritages of the past are detting less known by the present generation. One of which is a pawukon figures and their aesthetic values. Pawukon is a Javanese prediction or calculation based on Hindu mythology regarding time and its association with the prediction of human life based on their wuku (time characteristics). There are 30 pawukon figures, from the Wuku Sinta figure to Wuku Watugunung figure accompanied by a picture of their respective deities. Pawukon figures can be found in primbon books or enlarged and displayed in the interiors of Javanese houses. Pawukon figures such as wayang purwa are equipped with figures of buildings or gedhong, figures of weapons, figures of various types of trees, birds and other figures which each have a certain purpose and meaning. The composition of the various elements makes the overall visuals very interesting to be explored regarding the concept of visual, visual aesthetics and meaning. The pawukon figures also needs to be studied aesthetically regarding to their placement in the Javanese home interior and how to develop them to be better known by the present generation. To explore the aesthetics and development of Pawukon figures, the concept of wangun (aesthetic) derived from the Javanese culture was used. The research findings were interesting because the pawukon figures have the wangun elements and wangun visual arrangenments, wangun placement, and the development of the pawukon figures which is related to the concept of wangun and ora wangun (not aesthetic) or aÃ¨ng (strange). Pawukon figures were made to remind people to be cautious, and their applications and development into interior design were meant to present the atmosphere of Java.